2022
DOI: 10.1109/access.2022.3178999
|View full text |Cite
|
Sign up to set email alerts
|

A System Deployment Model of Multi-CCD Automatic Optical Inspection for Economical Operations

Abstract: Overkill and leakage are common problems in automated optical inspection (AOI) systems that have harmed firms to devote in intensive manual reinspection and seek the best CCD setting, resulting in more costly and less effective AOI operations. This study proposed a two-stage AOI based inspection system deployment model of multi-charge coupled device (CCD) for cost reduction; that is, the strictness decision model of a single CCD in the operational stage and switch on/off decision model of a set of CCDs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…From the fusion experiments in this paper, it can be concluded that: (1) The LPT method performs more robustly than other fusion methods. (2)The IHS transform and PCA methods are more suitable for image fusion of color and gray images.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…From the fusion experiments in this paper, it can be concluded that: (1) The LPT method performs more robustly than other fusion methods. (2)The IHS transform and PCA methods are more suitable for image fusion of color and gray images.…”
Section: Discussionmentioning
confidence: 81%
“…Polarization detection can obtain intensity and polarization information of the target scene, which is conducive to identifying hidden objects. In recent years, more and more researchers have been committed to the study of multi-modal sensors, which have been widely used in industrial detection [1] , remote sensing [2] , biomedicine [3] , autonomous driving [4] , and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are still some automatic optical inspection methods that use a non-transfer learning architecture [ 12 , 13 , 14 ]. In [ 15 ], a deep convolutional neural network is trained to detect scratches on the optical fiber connector end-face.…”
Section: Related Workmentioning
confidence: 99%